Is the albanian economic growth influenced by importing countries growth? - Shahini, Ledjon; Shera, Adela; Memaj, Fatmir (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
International trade, as a major factor of openness, has a significant contribution to economic growth, especially nowadays when globalization is becoming a widespread phenomenon. Country’s trade openness can be analyzed from one side by the impact of our revenue growth, which will influence the growth of domestic demand for imported goods and from the other side the revenue growth of other countries which will affect the growth of imported goods and thus in the growth of exports of analyzing country. Exports impact is very important to be treated combined with exchange rate, as another indicator of international competitiveness of countries goods.